Elasticity of demand for cellular phone network access in Malaysia - Rusli Latimaha,; Zakaria Bahari, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study analyzes the elasticity of demand for cellular phone network access and the network effects in Malaysia. It uses quarterly data from 2003Q1 to 2011Q4 with 7 difference variables in two separate equations. The dependent variable is the penetration rate of cellular phone. From the analysis, we found that the penetration rates of cellular phone are strongly related to the factors highlighted in the study and all the variables are strongly significant. The F-test also suggested that the entity Fixed Effects Model (FEM) is the appropriate model and more preferred for this study. From the entity FEM analysis, all independent variables are significant. The price elasticity of demand, crossprice elasticity and income elasticity are elastic. The result also shows that the fixed-line is complementary and luxury goods to the cellular phone network in Malaysia and the networks externalities are strongly significant when we used number of subscriber as a proxy.